The physics of the mind and brain disorders : integrated neural circuits supporting the emergence of mind - Opris, Ioan (Medical research personnel); Casanova, Manuel F. (Springer, 2017)
This book covers recent advances in the understanding of brain structure, function and disorders based on the fundamental principles of physics. It covers a broad range of physical phenomena occurring in the brain circuits for perception, cognition, emotion and action, representing the building blocks of the mind. It provides novel insights into the devastating brain disorders of the mind such as schizophrenia, dementia, autism, aging or addictions, as well as into the new devices for brain repair. The book is aimed at basic researchers in the fields of neuroscience, physics, biophysics and clinicians in the fields of neurology, neurosurgery, psychology, psychiatry.- Resumé vydavatel
Keywords: mozek; nemoci mozku; centrální nervový systém; brain; brain diseases; central nervous system; elektronické knihy; sborníky; electronic books; papers of several authors